UNDIED LOVE: THE DIALOGUE BETWEEN I CORINTHIANS 11:23-25 WITH GRAVES IN SANGIHE THROUGH THE LENS OF THEOLOGY OF REMEMBRANCE - Ryanto Adilang; Andrea Elfata Ratulangi (Institut Agama Kristen Negeri Manado, 2025)
It should be understood that everything always comes with a risk. This applies to everything, from the simple to the most complex. Risk is even present in the effort to love and be loved by someone. The most painful risk of loving is when death comes to pick you up. The Sangihe community seems to have its own way to deal with this. However, this method has drawn pros and cons from many circles, namely by choosing an unusual location for a grave (near one's own residence). This study uses qualitative research methods and Theology of Remembrance theory as the main